Rapunzel syndrome in a paediatric patient - Ngo, Choon Woon; Syauki H,; Kumar MV, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Rapunzel syndrome, or generically known as trichobezoar, is a rare condition. It usually happens among teenage population. We are presenting a case report of Rapunzel syndrome that happened in a 4-year-old child. She was initially investigated for nephrotic syndrome, as she had high blood pressure and hypoalbuminaemia. However, it was later found out to be a trichobezoar, indirectly causing both hypertension and malnutrition. This condition demanded a combination of surgical and psychiatric discipline for diagnosis and its treatment.